The behaviour of block masonry under in-plane loading. (30th May 2019) - Capozucca, R.; Magagnini, E.
In the design of buildings, the strength of modern masonry under compression and shear is crucial for safety in seismic areas. Modern unreinforced masonry (MURM) built with perforated clay blocks may also be considered adequate in terms of withstanding seismic action. However, the performance of MURM is influenced by many parameters such as solid or perforated units and strength, deformability and thickness of mortar joints. In this paper, the strength of blockwork walls built with two types of perforated clay blocks, lateral surfaces toothed and smooth, and different mortar joints has been experimentally tested under loading in-plane. An extensive investigation based on compression tests and diagonal compression tests of blockwork walls has been carried out. The experimental results are presented and discussed. The response of blockwork walls under diagonal tests have been analysed comparing experimental data with that obtained with finite element method (FEM).